Trapped in the NETs: Multiple Roles of Platelets in the Vascular Complications Associated with Neutrophil Extracellular Traps - Christopher Sennett; Giordano Pula (Cells)
Neutrophil extracellular traps (NETs) have received significant attention in recent years for their role in both the immune response and the vascular damage associated with inflammation. Platelets have been described as critical components of NETs since the initial description of this physio-pathological response of neutrophils. Platelets have been shown to play a dual role as responders and also as stimulators of NETs. The direct interaction with DNA leads to the entrapment of platelets into NETs, a phenomenon that significantly contributes to the thrombotic complications of inflammation and neutrophil activation, while the direct and paracrine stimulation of neutrophils by platelets has been shown to initiate the process of NET formation. In this review, we provide a comprehensive description of our current understanding of the molecular mechanisms underlying the entrapping of platelets into NETs and, in parallel, the platelet-driven cellular responses promoting NET formation. We then illustrate established examples of the contribution of NETs to vascular pathologies, describe the important questions that remain to be answered regarding the contribution of platelets to NET formation and NET-dependent cardiovascular complication, and highlight the fundamental steps taken towards the application of our understanding of platelets’ contribution to NETs for the development of novel cardiovascular therapies.